The explicit and the implicit in language and speech - Liashchova, Liudmila (Cambridge Scholars Publishing, 2018)
Our ability to acquire a language - one of the most complex semiotic systems - is stunning. However, to describe and explain even a small fraction of this system and of this ability is a great challenge. This book brings together modified papers of seventeen university scholars from Belarus, Germany, Russia and Lithuania originally presented at an international conference held in Minsk, Belarus, in 2017, on different hidden and implicit aspects of language and the ways of disclosing and explicating them. Language is understood by them differently as a cognitive ability, a specific semiotic stru.